MPI LEADERSHIP PERSONAL BRANDING: BUILDING SCHOOL AUTHORITY AND REPUTATION THROUGH DIGITALLY LITERATE LEADERS - Muthi'ah Rahman; Rifka Jannatul Firdausiyah; Yusril Ihza Saputra; Unzilah Khomairotusshiyamah; Moh Holidi; Siti Nur Aviatun Hasanah; Najiburrahman (Jurnal Manajemen dalam Pendidikan, 2026)
This study aims to analyze the role of personal branding of leadership in Islamic Education Management (MPI) based on digital literacy in building the authority and reputation of schools. The method used is a qualitative approach with a case study design, with data collection techniques through observation and in-depth interviews with leaders, teachers, education staff, and institutional media managers. Data analysis was carried out through the stages of condensation, presentation, and verification using content analysis, discourse, and interpretative approaches. The results of the study indicate that effective personal branding of leadership is built through leader authenticity, digital literacy as a strategic instrument, and the integration of Islamic values. Authenticity strengthens trust and authority, digital literacy enables the management of public narratives in a targeted manner, while Islamic values ​​serve as the foundation for building institutional credibility. The implications of this study emphasize that strengthening personal branding based on values ​​and increasing digital literacy are important factors in building a school's reputation that is adaptive and competitive in the digital era.